A tailor-made Successive Self-nucleation and Annealing protocol for the characterization of recycled polyolefin blends. (26th August 2020) - Carmeli, Enrico; Tranchida, Davide; Albrecht, Andreas; Müller, Alejandro J.; Cavallo, Dario
Abstract: A fast and easy-to-implement technique able to investigate the complex chemical composition of polyethylene/polypropylene (PE/PP) blends derived from recycling is required. Thermal fractionation, in particular the Successive Self-nucleation and Annealing (SSA) method, proves to be suitable for this purpose. Therefore, a new tailor-made SSA protocol, able to fractionate both PE and PP in the same temperature program, was developed. Furthermore, the fractionation of model blends with known composition allowed the assessment of the temperature regions where co-crystallization among the blend components does not occur, enabling the development of a method for the quantitative evaluation of the amount of the high melting PE component and of the PP phase in a blend. Finally, the composition of two recycled blends was successfully assessed by means of the novel quantitative method and the results were compared with those achieved by a solution-based fractionation technique on the same materials. Graphical abstract: Image 1 Highlights: Thermal fractionation of model and recycled PE/PP blends via tailor-made Successive Self-nucleation and Annealing (SSA). Linear PE fraction with the longest methylene sequence do not co-crystallize with PE copolymers. A DSC/SSA method for quantitative determination of recycled blends composition was developed. Results from the proposed SSA thermal fractionation in agreement with solution-based techniques (TREF).